Rolapitant for the prevention of nausea in patients receiving highly or moderately emetogenic chemotherapy. (23rd May 2018) - Navari, Rudolph M.; Rapoport, Bernardo L.; Powers, Dan; Arora, Sujata; Clark‐Snow, Rebecca
Abstract: Most patients receiving highly or moderately emetogenic chemotherapy experience chemotherapy‐induced nausea and vomiting without antiemetic prophylaxis. While neurokinin‐1 receptor antagonists (NK‐1RAs) effectively prevent emesis, their ability to prevent nausea has not been established. We evaluated the efficacy of the long‐acting NK‐1RA rolapitant in preventing chemotherapy‐induced nausea using post hoc analyses of data from 3 phase 3 trials. Patients were randomized to receive 180 mg oral rolapitant or placebo approximately 1‐2 hours before chemotherapy in combination with a 5‐hydroxytryptamine type 3 RA and dexamethasone. Nausea was assessed by visual analog scale during the acute (≤24 hours), delayed (>24‐120 hours), and overall (0‐120 hours) phases. Post hoc analyses by treatment group (rolapitant vs control) were performed on pooled data within patient subgroups receiving cisplatin‐based, carboplatin‐based, or anthracycline/cyclophosphamide (AC)‐based chemotherapy. In the cisplatin‐based chemotherapy group, significantly more patients receiving rolapitant than control reported no nausea (NN) in the overall (52.3% vs 41.7% [ P < .001]; absolute benefit [AB] = 10.6%), delayed (55.7% vs 44.3% [ P < .001]; AB = 11.4%), and acute (70.5% vs 64.3% [ P = .030]; AB = 6.2%) phases. Similar results were observed in the carboplatin‐based chemotherapy group, with significantly more patients receiving rolapitant than control reporting NN in the overall (62.5% vs 51.2% [ P = .023]; AB = 11.3%) and delayed (64.1% vs 53.6% [ P = .034]; AB = 10.5%) phases. In the AC‐based chemotherapy group, patients receiving rolapitant or control reported similar NN rates during the overall and delayed phases. Rolapitant effectively prevents nausea during the overall and delayed phases in patients receiving cisplatin‐ or carboplatin‐based chemotherapy. Abstract : While neurokinin‐1 receptor antagonists (NK‐1 RAs) effectively prevent emesis, their ability to prevent nausea has not been established. We evaluated the efficacy of the long‐acting NK‐1 RA rolapitant in preventing chemotherapy‐induced nausea using post hoc analyses of data from three phase 3 trials of patients receiving either cisplatin‐based, carboplatin‐based, or anthracycline/cyclophosphamide (AC)‐based chemotherapy. Rolapitant effectively prevented nausea during the overall and delayed phases in patients receiving cisplatin‐ or carboplatin‐based chemotherapy.